QAWL QADIM DAN QAWL JADID TENTANG HAJI DAN UMRAH DALAM MAZHAB ASY SYAFI’IY - Nasution, Goloman (Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract: For further explanation given to the Prophet SAW that throughout his life every case and the problems that arise can be resolved based on the Qur'an and Sunnah. However, in subsequent periods, the community and development changes so rapidly. Islamic empire expanded and the friends were scattered to various regions along with the current expended they do. Besides active in jihad and preach, the companions also assume responsibility for leading reference Fatwa and religious information. In the next period as a reference responsibilities shifted to the figures Tabi'in onwards to the mujtahid of the next generation. Syafi'iy Ash, who was born in Palestine in Gaza major H 150 in Mecca, long enough to learn by Imam Malik in Medina, had worked in Yemen, several times came to Baghdad and finally died in Egypt in 204 AH Syafi'iy Ash in the famous schools of the terms and Qawl qadim Qawl Jadid. The main problem discussed in this paper how the development of Islamic legal thought in the schools Ash Syafi'iy of Hajj and Umrah. Examples of changes from the fatwa Syafi'iy Ash and Qawl qadim Qawl Jadid about Hajj and Umrah can be expressed in some topic of discussion with the tendency that the arguments in Syafi'iy Ash fatwa change the dominant use ra'yu than using verse or hadith as the basis. In general, faktors that influence these changes due to the fatwa theorem, both the Qur'an and hadith that are used, social conditions, culture, customs. ملخص :القرآن أنزل على النبي محمد تحتوي على العقائد الأساسية، والأخلاق والقانون. لمزيد من التوضيح نظرا لأنه رأى النبي طوال حياته كل حالة من الحالات والمشاكل التي تنشأ لا يمكن أن تحل على أساس القرآن والسنة. ومع ذلك، في الفترات اللاحقة، وتنمية المجتمع والتغيرات بهذه السرعة. الإمبراطورية الإسلامية الموسعة والأصدقاء كانت متناثرة في مناطق مختلفة جنبا الى جنب مع انتشار الحالي لما فعلوه. إلى جانب نشط في الجهاد والدعوة، والمرافقون أيضا تحمل مسؤولية قيادة مرجعية الفتوى والمعلومات الدينية. في الفترة المقبلة باعتبارها مسؤوليات المرجعية انتقلت إلى الحرف صديق وهلم جرا إلى المجتهد للجيل القادم. مدرسة الإمام هذا واحد ولد في فلسطين في قطاع غزة الكبرى 150 ه في مكة المكرمة، وهي فترة كافية ليتعلم من الإمام مالك في المدينة المنورة، وقد عملت في اليمن، عدة مرات وجاء الى بغداد، وأخيرا توفي في مصر سنة 204 ه في هذه المدرسة الشهيرة في الفترة السابقة والقول القول الجديد. المشكلة الرئيسية التي نوقشت في هذه الورقة كيفية تطوير الفكر القانوني الإسلامي في مدرسته عن الحج والعمرة. أمثلة على التغيرات التي طرأت على فتوى من الأحكام السابقة وأحكام الحج والعمرة يمكن التعبير عنه في بعض الموضوع مطروح للنقاش مع احتمال أن تكون حجته في فتواه تغيير المهيمنة استخدام رءي من استخدام الآية أو الحديث كأساس. في العام، العوامل التي تؤثر هذه التغييرات نتيجة لنظرية الفتوى، فإن كلا من القرآن والحديث التي يتم استخدامها، والظروف الاجتماعية، والثقافة، والعادات.Kata Kunci: qawl qadim, qawl jadid, haji, umrah.